PEMBERDAYAAN KELUARGA DALAM MENURUNKAN TINGKAT KECEMASAN PASIEN GGK DENGAN HEMODIALISA - Wulandari, Oktavia; Widayati, Dhina (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Chronic kidney failure (CKD) is a pathological condition in the kidney with diverse etiologies, resulting in progressive decline in kidney function, and in general must undergo hemodialysis therapy. In patients with hemodialysis therapy, anxiety often arises with the therapeutic procedures that are given so that the system needs support from the family. This study wanted to determine the effect of family empowerment on anxiety levels of chronic renal failure patients with hemodialysis. The pre-experimental design was the design in this study with a population of 36 patients and a sample size of 22 patients obtained through purposive sampling. This study used a questionnaire instrument and the data obtained were analyzed using the Wilcoxon Sign Rank Test. The measurement results on the level of anxiety before the intervention showed 63% in the level of severe anxiety and after the intervention showed 46% in the category of moderate anxiety. P-value in the statistical test shows 0.003 which means that there is an influence of family empowerment with anxiety level of CRF patients undergoing hemodialysis therapy. Family empowerment can reduce the level of anxiety for patients undergoing hemodialysis in the Hemodialysis Room of RSUD. Mardi Waluyo Blitar. Family empowerment provides assistance, solutions, support, so that it can be used to overcome the anxiety experienced by patients undergoing hemodialysis.